Analysis of Individual Competence, Motivation, and Team Effectiveness in Human Resource Development to Support the Regeneration of Medan Theater Members - Gilang Ramadani; Emi Wakhyuni; Soulthan Saladin Batubara (Journal of Management, Economic, and Accounting, 2026)
The sustainability of arts organizations is largely determined by the success of their member regeneration processes. In the context of Medan Teater, regeneration depends not only on the recruitment of new members but also on the quality of human resource development, which is influenced by individual competence (X1), motivation (X2), and team effectiveness (X3). This study aims to analyze the effects of individual competence, motivation, and team effectiveness on human resource development (Y) in supporting the regeneration of Medan Teater members. This research employs a quantitative approach with a causal associative design. The respondents consisted of 54 members of Medan Teater, selected using the sampling technique applied in this study. Data were collected through Likert-scale questionnaires. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis, including t-tests, F-tests, and the coefficient of determination (R²), with the assistance of the SPSS program. The results indicate that, partially, individual competence, motivation, and team effectiveness have a positive and significant effect on human resource development. Simultaneously, these three independent variables also exert a significant influence on human resource development in supporting member regeneration. Accordingly, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. These findings suggest that successful regeneration at Medan Teater requires the enhancement of individual competencies, the strengthening of motivation, and effective teamwork as the primary foundations of the member development process.